Hubungan Frekuensi Pemberian ASI Terhadap Peningkatan Produksi ASI Secara Holistik Pada Ibu Menyusui - Miskiyah Tamar; Puji Setya Rini (IKesT Muhammadiyah Palembang, 2022)
The process of breast milk production is influenced by several factors including nutritional factors, breast care, socio-cultural factors, socio-cultural factors, breastfeeding factors/frequency of breastfeeding and psychological factors. The frequency of breastfeeding is one of the factors to increase breast milk, namely by breastfeeding children regularly. This research was conducted using descriptive analytic method, namely connecting between variables using a cross sectional approach. The independent variable in this study is the frequency of breastfeeding and the dependent variable is the increase in breast milk production. The results of the bivariate analysis of a total of 56 respondents using the Chi-Square Test obtained p value = 0.002, because the p value <0.05, statistically it can be said that there is a relationship between the frequency of breastfeeding and increased milk production.